(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
This study analyzed soil salinity dynamics in Hatiya Sub-district using Sentinel-2 imagery and Dynamic World land-cover data processed in Google Earth Engine. Cloud-masked seasonal composites, salinity indices and classification were generated in GEE and further refined in ArcGIS Pro. Post-classification comparison between 2018-19 and 2023-24 revealed a decline in low-salinity areas and substantial expansion of moderate salinity zones. The findings highlight accelerating salinity stress and provide essential baseline information for coastal land-management planning. Bangladesh J. Nuclear Agric,39(2): 169-177, 2025